Elliptical Undulator HU256 for Synchrotron Soleil: Magnetic Design, Computations and Measurements - Churkin, I.; Batrakov, A.; Briquez, F.; Chubar, O.; Dael, A.; Ilyin, I.; Kolokolnikov, Y.; Rouvinski, E.; Semenov, E.; Steshov, A.; Vobly, P. (IEEE transactions on applied superconductivity, 2006)
The paper describes the design, magnetic computations and measurements of the elliptical undulator HU256 for Synchrotron Soleil (France): the new technology for insertion vacuum chamber has permitted the design of a Bx & Bz dipole closed structure for an electromagnetic undulator. This magnetic design has been realized on the basis of the 2-D, 3-D modeling (Mermaid and RADIA codes), and dependence's of the magnetic field integrals from the main macroscopic parameters have been obtained. The undulator can work in standard and quasi-periodical modes. The single dipoles and the undulator HU256 were magnetically measured by a Hall probes system. The results of magnetic measurements and computations are compared and analyzed